2012
DOI: 10.1007/s10633-012-9363-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of test duration on the visual-evoked potential (VEP) and alpha-wave responses

Abstract: Primary objective The purpose of this study was to assess the effect of test duration on the visual-evoked potential (VEP) and related alpha power spectrum measures. Design and methods Two conditions (eyes-closed and eyes-open) were tested using four different durations: ten, twenty, forty-five, and sixty seconds. The Diopsys™ NOVA-TR system was used to obtain the visual-evoked potential (VEP) and extracted alpha-wave with its related power spectrum. 16 visually-normal, young-adult subjects (ages 22 to 25 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(50 citation statements)
references
References 40 publications
(61 reference statements)
5
45
0
Order By: Relevance
“…Lastly, the mean coefficient of variation (CV) values across all alpha wave frequencies and across all subjects ranged from 0.48-0.64, which was relatively small; this suggested good repeatability of the alpha wave responses. Thus, the Willeford et al [28,29] studies demonstrated that the VEP alpha wave component provided a reliable, objective correlate of human visual attention and, furthermore, significantly correlated with the subjective VSAT percentile score.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Lastly, the mean coefficient of variation (CV) values across all alpha wave frequencies and across all subjects ranged from 0.48-0.64, which was relatively small; this suggested good repeatability of the alpha wave responses. Thus, the Willeford et al [28,29] studies demonstrated that the VEP alpha wave component provided a reliable, objective correlate of human visual attention and, furthermore, significantly correlated with the subjective VSAT percentile score.…”
Section: Introductionmentioning
confidence: 94%
“…amplitude and latency) [19,45,46] and alpha band (8-13 Hz) power [28,29,40]. This system was used to generate an alternating checkerboard stimulus pattern, record the cortical responses and analyse the data.…”
Section: Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…30,31 The system consists of a 17·15 (horizontal·vertical) degree display monitor for stimulus presentation, a second monitor for use by the experimenter for data viewing, and a computer for stimulus generation, analysis, and graphical display. The Diopsys system is available commercially and is approved by the Food and Drug Administration for both research and clinical use.…”
Section: Apparatusmentioning
confidence: 99%